Pengaruh Lama Perendaman Air Kelapa Muda Terhadap Pertumbuhan Stek Bibit Vanili (Vanilla Planifolia Andrews) - Angga Firando (Jurusan Budidaya Perkebunan, 2021)
This study was conducted to determine the appropriate duration of immersion in young coconut water on the growth of vanilla seed cuttings. This research was conducted at the Payakumbuh State Agricultural Polytechnic Experimental Garden in March – June 2021. The experiment used a one-factor completely randomized design (CRD) with five replications. The experimental units were five levels of immersion time, 2 hours of immersion (P1), 4 hours of immersion (P2), 6 hours of immersion (P3), 8 hours of immersion (P4), and 10 hours of immersion (P5). Parameters observed were shoot emergence, root emergence, internode growth, shoot diameter, root wet weight, and shoot wet weight. The results showed that the immersion time of young coconut water with 10 hours of immersion (P5) was able to produce better seedling growth compared to other treatments in each parameter of observation.